2002
DOI: 10.1095/biolreprod67.2.534
|View full text |Cite
|
Sign up to set email alerts
|

Full-Term Development of Golden Hamster Oocytes Following Intracytoplasmic Sperm Head Injection

Abstract: The golden hamster is the mammalian species in which intracytoplasmic sperm injection (ICSI) was first tried to produce fertilized oocytes. Thus far, however, there are no reports of full-term development of hamster oocytes fertilized by ICSI. Here we report the birth of hamster offspring following ICSI. Keys to success were 1) performing ICSI in a dark room with a small incandescent lamp and manipulating both oocytes and fertilized eggs under a microscope with a red light source and 2) injecting sperm heads w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 31 publications
2
64
0
1
Order By: Relevance
“…In studies using rodent sperm, injection of whole sperm (mouse (Kimura & Yanagimachi 1995, Kuretake et al 1996) or of a sperm head (mouse (Kuretake et al 1996), rat (Hirabayashi et al 2002, Nakai et al 2005, and hamster (Yamauchi et al 2002)) is sufficient to generate full-term development. These results suggest that in these species, a large part of the activating stimulus resides in the sperm head.…”
Section: Introductionmentioning
confidence: 99%
“…In studies using rodent sperm, injection of whole sperm (mouse (Kimura & Yanagimachi 1995, Kuretake et al 1996) or of a sperm head (mouse (Kuretake et al 1996), rat (Hirabayashi et al 2002, Nakai et al 2005, and hamster (Yamauchi et al 2002)) is sufficient to generate full-term development. These results suggest that in these species, a large part of the activating stimulus resides in the sperm head.…”
Section: Introductionmentioning
confidence: 99%
“…A salient difference between natural and ICSI fertilization is that, in the latter, the sperm plasma membrane as well as acrosome (which contains a spectrum of powerful hydrolyzing enzymes) are introduced into an oocyte. For species with small acrosomes, injection of the acrosome into an oocyte apparently does not produce serious problems, but for species like the hamster, with very large acrosomes, injection inevitably results in death of the oocyte (3). We had demonstrated that the contents of the acrosome are potentially harmful to oocytes (4).…”
mentioning
confidence: 99%
“…Several reports showed higher efficiency in mouse and human ICSI following removal of the acrosomal vesicle [18,29,32], which rested on the assumption that its hydrolytic enzymes could harm the oocytes [25,37]. Notwithstanding that ionomycin induces acrosomal reaction (as suggested by Rotem et al [26] and confirmed in our experiments), we reached the same blastocyst rate by injecting piezo-pulsed spermatozoa pretreated both with and without ionomycin (PPS: 15.6 % vs. PPS-I: 15.5 %).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in mice have stressed the importance of the membrane and acrosome's removal before ICSI [18,25]. Furthermore, the retention of spermatozoa membranes is known to delay oocyte activation in mouse and human model [19,38], and the acrosomal enzymes are harmful to hamster oocytes [25,37]. In this work, we investigated whether the presence of the plasma membrane and the sperm acrosomal vesicle could be the limiting factors in sheep ICSI.…”
Section: Introductionmentioning
confidence: 99%